Graded recovery method for lithium, iron, phosphorus and graphite in waste lithium iron phosphate battery

By combining oxidative roasting and selective leaching technology, the problem of efficient recovery of lithium resources in waste lithium iron phosphate batteries is solved, and the grading recycling of iron, phosphorus and graphite is achieved through wet ball milling and secondary acid leaching technology, and the added value of recycling is increased.

CN119725837AActive Publication Date: 2025-03-28ZHEJIANG UNIV

Patent Information

Application Number
CN202411913990.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

It is difficult for the existing technology to efficiently recover lithium resources in waste lithium iron phosphate batteries while achieving coordinated high-value utilization of iron and phosphorus resources, resulting in low added value for recycling.

Method used

The combination of oxidative calcination and selective leaching is adopted to improve the leaching rate and selectivity of lithium, and iron and phosphorus are separated from graphite through wet ball milling and secondary acid leaching methods to achieve grading recovery.

Benefits of technology

The ultimate recovery of lithium is achieved, with the lithium leaching rate close to 100%, and the recovery efficiency of iron, phosphorus and graphite is improved, and high value-added products such as iron oxide and sodium phosphate salt are prepared.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725837A_ABST
    Figure CN119725837A_ABST
Patent Text Reader

Abstract

The invention relates to a waste lithium iron phosphate battery recycling method, in particular to a graded recycling method for lithium, iron, phosphorus and graphite in a waste lithium iron phosphate battery, and belongs to the technical field of lithium ion batteries and resource recycling of the lithium ion batteries. According to the method, the mode that oxidizing roasting and selective leaching are combined is adopted, the leaching rate and selectivity of lithium are effectively improved, the leaching rate of the lithium element is close to 100% under the optimized condition, and limit recovery of the lithium element is achieved; meanwhile, aiming at the problem that iron and phosphorus in the leaching residues are difficult to utilize, a wet ball milling and secondary acid leaching method is combined, phosphorus and iron elements are separated from negative electrode graphite firstly, and graded recovery of iron, phosphorus and graphite is achieved. According to the method, the high recovery rate of lithium is realized, and meanwhile, high-added-value products such as ferric oxide and sodium phosphate are prepared by efficiently recovering ferric phosphate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for recycling waste lithium iron phosphate batteries, in particular to a method for graded recovery of lithium, iron, phosphorus and graphite in waste lithium iron phosphate batteries, belonging to the technical field of lithium ion batteries and resource recycling. Background Art

[0002] High-quality recycling of retired lithium batteries is of great significance in supporting the sustainable development of the new energy industry.

[0003] Among lithium batteries, lithium iron phosphate batteries are widely used in electric vehicles, ships, UPS uninterruptible power supplies and other fields due to their high safety, long cycle life and low cost. The recycling of waste lithium iron phosphate batteries has also received more and more attention. By recycling waste lithium iron phosphate batteries, we can reduce the waste of resources, reduce environmental pollution and achieve sustainable development.

[0004] At present, the recycling process for waste lithium iron phosphate batteries can be divided into pyrometallurgical recycling process, hydrometallurgical recycling process and repair and regeneration process; the three processes have their own advantages and disadvantages, but comprehensively comparing the above three technologies, the hydrometallurgical recycling process is considered to be an ideal recycling method due to its low energy consumption, high recycling efficiency and high product purity. It is also the main process for recycling waste lithium iron phosphate batteries at home and abroad.

[0005] Lithium iron phosphate battery materials only contain lithium, a high-value metal, and do not contain other high-value metals such as nickel, cobalt, and manganese. Previously, the high price of lithium has led to research focusing on wet-process lithium extraction. However, as lithium prices continue to fall, the economic benefits of simply recycling lithium elements in waste lithium iron phosphate battery positive electrode materials are not high. It is necessary to achieve the treatment of iron-phosphorus waste slag and the coordinated high-value utilization of graphite resources while efficiently and maximally recovering lithium resources to increase the added value of recycling. However, there is currently a lack of relevant mature processes that can simultaneously achieve the ultimate recovery of lithium and the high-value utilization of iron, phosphorus elements, and negative electrode graphite. Summary of the invention

[0006] The present invention aims at the difficulty of efficiently recovering lithium resources from waste lithium iron phosphate battery materials in the prior art while realizing the coordinated high-value utilization of resources such as iron and phosphorus, and proposes a method for graded recovery of lithium, iron, phosphorus and graphite in waste lithium iron phosphate batteries. The method adopts a combination of oxidative roasting and selective leaching to effectively improve the leaching rate and selectivity of lithium. Under optimized conditions, the leaching rate of lithium element is close to 100%, realizing the limit recovery of lithium element; at the same time, in view of the difficulty of utilizing iron and phosphorus in leached slag, wet ball milling combined with secondary acid leaching method is adopted to separate phosphorus and iron elements from negative electrode graphite first, realizing graded recovery of iron, phosphorus and graphite. The method realizes a high recovery rate of lithium, and at the same time, high-efficiency recovery of iron phosphate is prepared to obtain high value-added products such as iron oxide and sodium phosphate.

[0007] The technical solution adopted by the present invention to solve its technical problem is:

[0008] A method for graded recovery of lithium, iron, phosphorus and graphite in waste lithium iron phosphate batteries, the method comprising the following steps:

[0009] (1) Discharging the lithium iron phosphate battery: The lithium ion battery is discharged and the discharged lithium iron phosphate battery is dried at room temperature;

[0010] (2) Lithium iron phosphate battery crushing is done by crushing machine, and the crushing equipment is equipped with dust collection device, which does not pollute the outside world;

[0011] (3) Screening of the crushed lithium iron phosphate battery products, screening the crushed battery materials to obtain black powder (a mixture of positive and negative electrode materials), copper particles, aluminum particles, and separators;

[0012] (4) Oxidative calcination: calcining the black powder at a high temperature of 550-650°C for 120-300 minutes, with the oxygen concentration in the calcination atmosphere being ≥2%, so that the divalent iron ions are completely converted into trivalent iron to obtain the calcined battery black powder;

[0013] (5) Acid leaching of lithium: adding battery black powder to sulfuric acid for leaching to obtain a lithium-containing leaching solution and a leaching residue containing iron phosphate and negative electrode graphite; the concentration of sulfuric acid is 0.1-1 mol / L, the solid-liquid ratio of black powder to dilute sulfuric acid is 80-120 g / L, the reaction time is 240-300 minutes, and the temperature is 35-95°C;

[0014] (6) Deeply removing impurity elements from the leachate: adding 2-5 mol / L sodium hydroxide solution to the leachate to adjust the pH to between 6.5 and 7.5, stirring and filtering to obtain a decontaminated liquid and decontaminated residue;

[0015] (7) Evaporation and crystallization of the impurity removal liquid: adding saturated sodium carbonate to the impurity removal liquid and evaporating and crystallizing it to obtain solid lithium carbonate and sodium sulfate solution; the solid lithium carbonate can be further purified;

[0016] (8) Graded recovery of iron and phosphorus: wet ball milling of the leached residue containing iron phosphate and negative electrode graphite, the ball milling aid used in the wet ball milling is a mixture of oleic acid, oleylamine and heptane, wherein the volume ratio of the leached residue to the oleic acid, oleylamine and heptane in the ball milling aid is 1:1:10:20, tungsten carbide balls and tungsten carbide ball milling pots are used, and the weight ratio of tungsten carbide balls to the mixture is 60:1;

[0017] The powder obtained by wet ball milling is leached with sulfuric acid to separate graphite from iron and phosphorus, and a sodium hydroxide solution is added to the iron and phosphorus-containing leaching solution until no precipitate is generated in the leaching solution, and the iron hydroxide precipitate and phosphorus-containing waste liquid are filtered out; the iron hydroxide precipitate is roasted and dehydrated to obtain iron oxide; the phosphorus-containing waste liquid is adjusted to a pH between 7 and 9 with a 2-5 mol / L sodium hydroxide solution to obtain a sodium phosphate solution; the sodium phosphate solution is directionally converted into a sodium phosphate salt product in an incinerator.

[0018] Preferably, the discharge treatment method described in (1) is to immerse the sample in a 5-20wt.% sodium chloride or sodium sulfate solution for more than 48 hours, and then remove the sample for cleaning and drying after the discharge is complete.

[0019] Preferably, in (2), a jaw crusher or a hammer crusher is used for crushing.

[0020] Preferably, a sieve with a mesh size greater than 200 is used for screening in (3) to ensure that the battery black powder is completely separated from other materials and that the purity of the battery black powder is greater than 95%.

[0021] Preferably, the process of carbonization, cracking and refining of lithium carbonate described in (7) is: solid lithium carbonate is mixed with water to form a slurry, and CO2 is introduced from the bottom of the slurry during stirring. In the slurry, the weight ratio of solid lithium carbonate to water is not higher than 1:30, ensuring that low-purity lithium carbonate is fully dissolved and the purity of the introduced CO2 gas is not less than 99.99%.

[0022] Preferably, in (8), the ball milling frequency is 10-30 Hz, and the ball milling time is 120-300 minutes; the slurry obtained by wet ball milling is centrifuged at 8000 rpm for 5-10 minutes, washed with ethanol 4-6 times to separate the leached residue powder and the composite solvent, and vacuum dried for more than 10 hours; the concentration of sulfuric acid in the leaching process is 1-3 mol / L, the solid-liquid ratio of the leached residue powder to the dilute sulfuric acid is 80-120 g / L, the reaction time is 200-300 minutes, and the temperature is 70-95°C; the sodium phosphate solution forms sodium tripolyphosphate at an operating temperature of 500-600°C in an incinerator, forms sodium pyrophosphate at 600-700°C, forms trisodium phosphate at 700-800°C, and forms sodium hexametaphosphate at 800-850°C.

[0023] As a preferred method, (4) oxidative roasting: roast the black powder in air at 600°C for 240 minutes to completely convert the divalent iron ions into trivalent iron, and obtain the roasted battery black powder; (5) acid leaching of lithium: add sulfuric acid to the battery black powder for leaching to obtain a lithium-containing leaching solution and a leaching residue containing iron phosphate and negative electrode graphite; the concentration of sulfuric acid is 0.5 mol / L, the solid-liquid ratio of black powder to dilute sulfuric acid is 80-120 g / L, the reaction time is 300 minutes, and the temperature is 95°C. Under these conditions, 99.9% of the lithium in the crushed lithium iron phosphate battery black powder enters the leaching solution and is selectively extracted, and only 1.77% of phosphorus and 2.06% of iron enter the leaching solution, achieving selective leaching and extreme recovery of lithium.

[0024] The beneficial effects of the present invention are:

[0025] 1. In the present invention, in the process steps of oxidation roasting and selective lithium extraction, the leaching rate and selectivity of lithium are effectively improved by controlling the temperature and oxygen concentration of oxidation roasting and the concentration of leaching acid. At the same time, through deep impurity removal, evaporation crystallization, and carbonization purification, the purity of the final lithium carbonate product is greater than 99.6%, which effectively ensures the high purity of lithium carbonate.

[0026] 2. In the present invention, by controlling the frequency and time of wet ball milling, the particle size of the leached residue is reduced, and the leached residue is induced to transform from a crystalline phase to an amorphous phase, so that the iron phosphate in the leached residue is leached to the maximum extent, and the iron phosphate and the negative electrode graphite in the leached residue are effectively separated, so that both the iron phosphate and the negative electrode graphite can be recycled and reused.

[0027] 3. In the present invention, efficient recovery of lithium, iron, phosphorus and graphite in waste lithium iron phosphate batteries is achieved through step-by-step recovery of the entire process and directional conversion of phosphorus-containing waste liquid in the final process. Finally, the phosphorus-containing waste liquid is directionally converted into a sodium phosphate salt product through processes such as pH adjustment, atomization and incineration. No waste liquid is generated in the entire process, thus achieving full-element green recovery of waste lithium iron phosphate battery electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is the main process flow of the present invention;

[0029] Figure 2 It is the in-situ XRD spectrum of the black powder of lithium iron phosphate battery in the present invention after oxidation roasting in air atmosphere (test condition: 10°C / min);

[0030] Figure 3 The XRD spectra of the lithium iron phosphate positive electrode material after calcination in atmospheres with different oxygen contents in the present invention;

[0031] Figure 4Variation of element leaching efficiency of lithium iron phosphate material after air roasting with (a) hydrogen ion concentration, (b) leaching time and (c) leaching temperature (leaching conditions a: 35°C, 100 g / L, 5 min; b: 35°C, 100 g / L, 0.5 mol / L H2SO4; c: 100 g / L, 0.5 mol / L H2SO4, 300 min);

[0032] Figure 5 The effect of wet ball milling time and temperature on the particle size of leached residue in the present invention;

[0033] Figure 6 It is a comparison of the leaching rate of iron phosphate before and after wet ball milling in the present invention. DETAILED DESCRIPTION

[0034] The technical solution of the present invention is further described in detail below through specific embodiments. It should be understood that the implementation of the present invention is not limited to the following embodiments, and any form of modification and / or change made to the present invention will fall within the protection scope of the present invention.

[0035] In the present invention, unless otherwise specified, all parts and percentages are by weight, and the equipment and raw materials used can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.

[0036] The reagents used in the following examples, unless otherwise specified, can be purchased from conventional biochemical reagent stores.

[0037] For ease of comparison, the following article uses 18650 type of waste lithium iron phosphate batteries for testing.

[0038] Embodiment 1:

[0039] In this embodiment, lithium iron phosphate is calcined at 600° C. in an air atmosphere, and leached at 0.5 mol / L H 2 SO 4 for 300 minutes at 95° C. to recover lithium element in the form of lithium carbonate.

[0040] A method for recycling lithium, iron, phosphorus and graphite from waste lithium iron phosphate batteries, the process flow is as follows: Figure 1 As shown, the steps of this method are as follows:

[0041] S1: Discharging lithium iron phosphate batteries: Place the used lithium-ion batteries in a 10wt.% Na2SO4 aqueous solution and soak for more than 48 hours to ensure complete discharge;

[0042] S2: Lithium iron phosphate battery crushing. The discharged lithium iron phosphate battery is dried at room temperature for 48 hours and crushed by a jaw crusher. The crushing facility is equipped with a dust collection device, which does not pollute the outside world.

[0043] S3: Screening of lithium iron phosphate battery crushing products. The crushed battery materials are screened to obtain battery black powder, copper particles, aluminum particles and diaphragms respectively. A 250-mesh screen is used for screening to ensure that the battery black powder is completely separated from other materials, so that the black powder reaches 95% purity;

[0044] S4: Oxidation roasting: roasting the lithium iron phosphate battery black powder at 600°C in an air atmosphere for 240 minutes to completely convert the divalent iron ions into trivalent iron;

[0045] S5: Acid leaching of lithium, the calcined lithium iron phosphate battery black powder is placed in 0.5 mol / L sulfuric acid, the solid-liquid ratio of black powder to dilute sulfuric acid is 100 g / L, and reacts for 300 minutes in a 95°C water bath to obtain lithium leaching solution and leaching residue containing iron phosphate and negative electrode graphite;

[0046] S6: deeply removing impurity elements from the leachate, adding 2 mol / L sodium hydroxide solution to the acidic leachate containing lithium to adjust the pH value to neutral, and filtering to obtain a decontaminated solution containing lithium sulfate;

[0047] S7: adding saturated sodium carbonate to the impurity removal liquid and evaporating and crystallizing to obtain lithium carbonate solid and sodium sulfate solution; the purity of lithium carbonate is not less than 98.5%, meeting the requirements of GB / T 11075-2013 Lithium Carbonate.

[0048] S8: Iron and phosphorus graded recovery:

[0049] The leached residue containing iron phosphate and negative electrode graphite is mixed with a composite solvent (oleic acid, oleylamine and heptane) in a volume ratio of 1:1:10:20 to obtain a mixture; in order to avoid impurities during ball milling, tungsten carbide balls and pots are used, and the weight ratio of the balls to the mixture is 60:1;

[0050] The mixture was ball milled at a frequency of 30 Hz for 300 minutes in a ball mill to obtain a slurry; the slurry was washed with ethanol five times in a high-speed centrifuge (8000 rpm, 10 min) to separate the black powder and the composite solvent; after drying under vacuum for 10 h, a leached residue powder with a particle size of about 0.4 μm was obtained; the separated composite solvent was reused; the changes in the leached residue particle size and ball milling temperature with ball milling time are shown in FIG. Figure 5 As shown in the figure, with the increase of ball milling time, the particle size of the leached residue gradually decreases, and then tends to be stable near 0.4μm, indicating that ball milling effectively reduces the particle size of the leached residue, and the smaller particle size helps the leached residue to contact with sulfuric acid more fully in the subsequent process; at the same time, with the increase of ball milling time, the temperature of the leached residue also increases significantly, indicating that ball milling produces a mechanical activation effect, inducing the leached residue to transform from the crystalline phase to the amorphous phase, reducing the binding force of the crystals during the leaching process, and is beneficial to the subsequent leaching of iron phosphate in sulfuric acid.

[0051] The leached residue powder with a particle size of 0.4 μm is placed in 2 mol / L sulfuric acid and reacted in a water bath at 95°C for 240 minutes to fully dissolve it; sodium hydroxide solution is added to the solution until no precipitation is generated in the solution, and the iron hydroxide precipitation and phosphorus-containing waste liquid are filtered out;

[0052] The iron hydroxide precipitate is fully calcined at 500°C and completely dehydrated to obtain iron oxide.

[0053] The phosphorus-containing waste liquid is adjusted to pH 7-9 with sodium hydroxide solution to obtain sodium phosphate solution; the sodium phosphate solution is directionally converted into sodium phosphate salt products in the incinerator. The specific process is: using a two-fluid nozzle, compressed air is used to atomize the sodium phosphate solution (particle size is 0.2-0.5μm) and then sent to the incinerator. In the incinerator, by burning natural gas, the water in the sodium phosphate solution is evaporated to form sodium phosphate salt products. The selectivity of the sodium phosphate salt product is achieved by adjusting the operating temperature of the incinerator. Sodium tripolyphosphate is formed at an operating temperature of 500-600℃, sodium pyrophosphate is formed at 600-700℃, trisodium phosphate is formed at 700-800℃, and sodium hexametaphosphate is formed at 800-850℃. The purity of the sodium phosphate salt is higher than 96%.

[0054] Embodiment 2:

[0055] In this embodiment, lithium iron phosphate is calcined at 600° C. in an air atmosphere, and leached at 0.5 mol / L H2SO4 for 300 minutes at 95° C. to recover lithium elements in the form of high-purity lithium carbonate.

[0056] A method for graded recovery of lithium, iron, phosphorus and graphite in waste lithium iron phosphate batteries, the method comprising the following steps:

[0057] S1: Discharging lithium iron phosphate batteries: Place the used lithium batteries in a 10wt% Na2SO4 aqueous solution and soak for more than 48 hours to ensure complete discharge;

[0058] S2: Lithium iron phosphate battery crushing. The discharged lithium iron phosphate battery is dried at room temperature for 48 hours and crushed by a hammer crusher. The crushing facility is equipped with a dust collection device, which does not pollute the outside world.

[0059] S3: Screening of lithium iron phosphate battery crushing products. The crushed battery materials are screened to obtain battery black powder, copper particles, aluminum particles and diaphragms respectively. A 300-mesh screen is used for screening to ensure that the battery black powder is completely separated from other materials, so that the black powder reaches a purity of 98%;

[0060] S4: Oxidation roasting: roast the lithium iron phosphate battery black powder at a high temperature of 600°C for 240 minutes to completely convert the divalent iron ions into trivalent iron;

[0061] S5: Acid leaching of lithium, the calcined lithium iron phosphate battery black powder is placed in 0.5 mol / L sulfuric acid, the solid-liquid ratio of black powder to dilute sulfuric acid is 100 g / L, and reacts for 300 minutes in a 95°C water bath to obtain lithium leaching solution and leaching residue containing iron phosphate and negative electrode graphite;

[0062] S6: deeply removing impurity elements from the leachate, adding 2 mol / L sodium hydroxide solution to the acidic leachate containing lithium to adjust the pH value to neutral, and filtering to obtain a decontaminated solution containing lithium sulfate;

[0063] S7: evaporating and crystallizing the impurity removal liquid, adding saturated sodium carbonate to the impurity removal liquid, evaporating and crystallizing to obtain lithium carbonate solid and sodium sulfate solution;

[0064] Solid lithium carbonate is mixed with deionized water at a solid-liquid ratio of 1:30 to form a slurry, and then 99.999% CO2 gas is introduced from the bottom during stirring. CO2 reacts with lithium carbonate, which is slightly soluble in water, to convert into LiHCO3 with greater solubility. The reaction is carried out until the solid particles no longer dissolve, and a pure filtrate is obtained by filtering. The filtrate is stirred and heated to remove CO2, thereby precipitating lithium carbonate. After measurement, the purity of the purified lithium carbonate can reach 99.6%, which meets the requirements of "YS / T 582-2013 Battery Grade Lithium Carbonate".

[0065] S8: Iron and phosphorus graded recovery:

[0066] The leached residue containing iron phosphate and negative electrode graphite is mixed with a composite solvent (oleic acid, oleylamine and heptane) in a volume ratio of 1:1:10:20 to obtain a mixture; in order to avoid impurities during the ball milling process, tungsten carbide balls and pots are used, and the weight ratio of the balls to the mixture is 60:1; the mixture is ball milled in a ball mill at a frequency of 30 Hz for 240 minutes to obtain a slurry; the slurry is washed with ethanol in a high-speed centrifuge (8000 rpm, 10 min) for 5 times to separate the black powder and the composite solvent; after drying under vacuum for 10 hours, a leached residue powder with a particle size of about 0.4 μm is obtained; the separated composite solvent is reused;

[0067] The leached residue powder with a particle size of 0.4 μm is placed in 2 mol / L sulfuric acid and reacted in a water bath at 95°C for 240 minutes to fully dissolve it; sodium hydroxide solution is added to the solution until no precipitation is generated in the solution, and the iron hydroxide precipitation and phosphorus-containing waste liquid are filtered out;

[0068] The iron hydroxide precipitate is fully calcined at 500°C and completely dehydrated to obtain iron oxide.

[0069] The phosphorus-containing waste liquid is adjusted to pH 7-9 with sodium hydroxide solution to obtain sodium phosphate solution; the sodium phosphate solution is directionally converted into sodium phosphate salt products in the incinerator. The specific process is: using a two-fluid nozzle, compressed air is used to atomize the sodium phosphate solution (particle size is 0.2-0.5μm) and then sent to the incinerator. In the incinerator, by burning natural gas, the water in the sodium phosphate solution is evaporated to form sodium phosphate salt products. The selectivity of the sodium phosphate salt product is achieved by adjusting the operating temperature of the incinerator. Sodium tripolyphosphate is formed at an operating temperature of 500-600℃, sodium pyrophosphate is formed at 600-700℃, trisodium phosphate is formed at 700-800℃, and sodium hexametaphosphate is formed at 800-850℃. The purity of the sodium phosphate salt is higher than 96%.

[0070] The recovery rates of the products in Example 1 and Example 2 are shown in Table 1.

[0071] Table 1

[0072] Graphite recovery rate Lithium recovery rate Iron recovery rate Phosphorus recovery rate Example 1 97.65% (preliminary) 94.91% 96.21% 99.6% Example 2 97.32% (preliminary) 91.89% 95.05% 99.5%

[0073] The initial meaning of graphite recovery rate is that the crude graphite recovered by this method needs to be finely processed later.

[0074] The crushed and screened lithium iron phosphate battery black powder was placed in a tunnel furnace for calcination. The calcination atmosphere was air. The calcination temperatures were 30℃, 100℃, 200℃, 300℃, 400℃, 500℃, 600℃, 700℃, 800℃, and 900℃ respectively; in order to investigate the difference in effects of different calcination temperatures.

[0075] The in-situ XRD results of lithium iron phosphate battery black powder in air atmosphere are as follows Figure 2 As shown. At 30-300°C, the lithium iron phosphate does not change its crystal phase and remains LiFePO4 (JCPDS#40-1499), with the main exposed crystal face being the (121) face. When the temperature rises to above 300°C, the diffraction peak of the original lithium iron phosphate crystal phase gradually weakens, indicating that the lithium iron phosphate is gradually being oxidized. Until the temperature reaches 600°C, the original lithium iron phosphate crystal phase is completely transformed into a high-valent iron compound, and the diffraction peaks of Li3Fe2(PO4)3 (JCPDS#47-0107) with an exposed crystal face of (002) and Fe2O3 (JCPDS#72-0469) with an exposed crystal face of (02) appear. Since the heating program is not paused during the detection process, the diffraction peak of the new crystal phase gradually becomes clearer with the increase of temperature and the extension of time.

[0076] By comparing Example 1 and Comparative Example 1, it is found that 600°C is a boundary temperature that causes the lithium iron phosphate crystal phase to change. Temperatures below 600°C do not cause the lithium iron phosphate crystal phase transformation, which will affect the lithium selectivity during the acid leaching process.

[0077] Comparative Example 2 Investigation of the Calcination Atmosphere of Black Powder for Lithium Iron Phosphate Batteries

[0078] The crushed and sieved lithium iron phosphate battery black powder was placed in a tunnel furnace and roasted at a temperature of 600°C. The roasting atmospheres (in terms of volume percentage) were pure nitrogen (0% oxygen), 0.1% oxygen (the rest was nitrogen, and the same was true for other proportions of oxygen), 0.2% oxygen, 0.5% oxygen, 0.8% oxygen, 1% oxygen, 2% oxygen, 21% oxygen, and 100% oxygen to investigate the effects of different oxygen concentrations.

[0079] The calcined products under different atmospheres were subjected to XRD analysis. The results are as follows: Figure 3 As shown. It was found that calcination in a nitrogen atmosphere did not change the main crystal phase of lithium iron phosphate LiFePO4 (JCPDS#40-1499), and the main exposed crystal plane was the (121) plane. As the oxygen content in the atmosphere increased to 2% or more, high-valent iron oxide Fe2O3 (JCPDS#33-0664) and trivalent iron lithium iron phosphate Li3Fe2(PO4)3 (JCPDS#47-0107) appeared in the spectrum. The former was mainly exposed at the (104) plane, and the latter was mainly exposed at the (002) plane. This shows that when the oxygen concentration in the calcination atmosphere increases to more than 2%, oxygen begins to react with lithium iron phosphate. The original lithium iron phosphate crystal phase is destroyed, and high-valent iron oxides and compounds appear.

[0080] Therefore, the black powder of lithium iron phosphate battery can be roasted by air roasting.

[0081] Comparative Example 3 Investigation of Process Parameters for Acid Leaching of Lithium

[0082] During the acid leaching of lithium in step S5, the leaching acid concentration, leaching time and leaching temperature were changed in turn to investigate the effects of the leaching acid concentration, leaching time and leaching temperature on the leaching property and selectivity of lithium in the leaching process.

[0083] Figure 4 The results show that the air-baked lithium iron phosphate + / Li + The leaching behavior of elements under water. In water, almost no elements are leached, but when the hydrogen ion concentration slowly increases, the leaching efficiency of lithium, phosphorus, and iron increases in turn. When the hydrogen ion concentration in the solution (cH + ) is approximately equal to the lithium ion concentration (cLi +) (the sulfuric acid concentration is 0.5 mol / L at this time), a high lithium leaching rate and lithium selectivity can be achieved. This shows that the oxidation roasting product does not generate water-soluble lithium compounds, and lithium needs to be dissolved using hydrogen ions. Based on this condition, the leaching time is extended, such as Figure 4 As shown in (b), the leaching rates of lithium and phosphorus continue to increase, while iron reaches equilibrium in a relatively short time. Finally, the leaching rates of the three elements stabilize within 300 minutes after leaching. Figure 4 c), it was found that the leaching rate of lithium increased with the increase of temperature, reaching 100% at 95°C. In addition, the leaching rate of phosphorus dropped from 80% to 0%, and the leaching rate of iron dropped from 9% to 0%. This is because as the temperature rises, the iron element continues to dissolve in 0.5 mol / L dilute sulfuric acid. As the reaction proceeds, the hydrogen ions in the solution are continuously consumed, and the pH gradually increases. Ferric phosphate will form a precipitate when the pH is 3-5, and the phosphorus element in the solution is gradually dissolved into the iron in the liquid phase, forming an iron phosphate precipitate in the solid phase residue. At this time, only lithium exists in the solution, so the selectivity of lithium increases with the increase of leaching temperature, and finally a lithium leaching rate of more than 99.9% is achieved at 95°C, with a selectivity of 97.56%.

[0084] Comparison of Examples 1 and 2 with Comparative Examples 1, 2 and 3 confirms that the calcination atmosphere and calcination temperature of the oxidative calcination, as well as the concentration of the leaching acid, the leaching time and the leaching temperature of the leaching process all have an effect on the selective leaching of lithium from the black powder of the lithium iron phosphate battery. Therefore, the optimal process parameters of the graded recovery method are: 600°C air calcination for 240 minutes, and the use of 0.5 mol / L dilute sulfuric acid (at this time, the hydrogen ion concentration in the solution (cH + ) is approximately equal to the lithium ion concentration (cLi + )), leached for 300 minutes at 95°C, at which time, 99.9% of the lithium in the crushed lithium iron phosphate battery black powder entered the leaching solution and was selectively extracted. At the same time, only 1.77% of phosphorus and 2.06% of iron entered the leaching solution, achieving selective leaching and extreme recovery of lithium.

[0085] Comparative Example 4

[0086] In the graded recovery of S8 iron and phosphorus, ball milling was not used. 2 mol / L sulfuric acid was used directly to leach the leaching residue to investigate the effect of ball milling on the leaching rate of iron phosphate.

[0087] Figure 6The comparison of the leaching rate of iron phosphate before and after wet ball milling is shown in the figure. It is found that under the same leaching time, the leaching efficiency of iron phosphate in the ball-milled leaching residue is significantly higher than that in the non-ball-milled leaching residue. This is because ball milling reduces the particle size of the leaching residue, inducing the leaching residue to transform from a crystalline to an amorphous phase. The mechanical activation effect of ball milling enables the iron phosphate in the leaching residue to be leached to the maximum extent.

[0088] The above is a detailed introduction to the hierarchical recovery method of lithium, iron, phosphorus and graphite in waste lithium iron phosphate batteries provided by the present invention. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for recycling lithium, iron, phosphorus and graphite from waste lithium iron phosphate batteries, characterized in that The method comprises the following steps: (1) Discharging the lithium iron phosphate battery: The lithium ion battery is discharged and the discharged lithium iron phosphate battery is dried at room temperature; (2) Lithium iron phosphate battery crushing is done by crushing machine, and the crushing equipment is equipped with dust collection device, which does not pollute the outside world; (3) Screening of the crushed lithium iron phosphate battery products, screening the crushed battery materials to obtain black powder, copper particles, aluminum particles, and diaphragms; (4) Oxidative calcination: calcining the black powder at a high temperature of 550-650°C for 120-300 minutes, with the oxygen concentration in the calcination atmosphere being ≥2%, so that the divalent iron ions are completely converted into trivalent iron to obtain the calcined battery black powder; (5) Acid leaching of lithium: adding battery black powder to sulfuric acid for leaching to obtain a lithium-containing leaching solution and a leaching residue containing iron phosphate and negative electrode graphite; the concentration of sulfuric acid is 0.1-1 mol / L, the solid-liquid ratio of black powder to dilute sulfuric acid is 80-120 g / L, the reaction time is 240-300 minutes, and the temperature is 35-95°C; (6) Deeply removing impurity elements from the leachate: adding 2-5 mol / L sodium hydroxide solution to the leachate to adjust the pH to between 6.5 and 7.5, stirring and filtering to obtain a decontaminated liquid and decontaminated residue; (7) Evaporation and crystallization of the impurity removal liquid: adding saturated sodium carbonate to the impurity removal liquid and evaporating and crystallizing it to obtain solid lithium carbonate and sodium sulfate solution; the solid lithium carbonate can be further purified; (8) Graded recovery of iron and phosphorus: wet ball milling of the leached residue containing iron phosphate and negative electrode graphite, the ball milling aid used in the wet ball milling is a mixture of oleic acid, oleylamine and heptane, wherein the volume ratio of the leached residue to the oleic acid, oleylamine and heptane in the ball milling aid is 1:1:10:20, tungsten carbide balls and tungsten carbide ball milling pots are used, and the weight ratio of tungsten carbide balls to the mixture is 60:1; The powder obtained by wet ball milling is leached with sulfuric acid to separate graphite from iron and phosphorus, and a sodium hydroxide solution is added to the iron and phosphorus-containing leaching solution until no precipitate is generated in the leaching solution, and the iron hydroxide precipitate and phosphorus-containing waste liquid are filtered out; the iron hydroxide precipitate is roasted and dehydrated to obtain iron oxide; the phosphorus-containing waste liquid is adjusted to a pH between 7 and 9 with a 2-5 mol / L sodium hydroxide solution to obtain a sodium phosphate solution; the sodium phosphate solution is directionally converted into a sodium phosphate salt product in an incinerator.

2. The classification recovery method according to claim 1, characterized in that: (1) The discharge treatment method is to immerse the sample in a 5-20wt.% sodium chloride or sodium sulfate solution for more than 48 hours, and then take it out for cleaning and drying after the discharge is complete.

3. The classification recovery method according to claim 1, characterized in that: (2) A jaw crusher or a hammer crusher is used for crushing.

4. The classification recovery method according to claim 1, characterized in that: (3) Use a sieve with a mesh size greater than 200 for screening to ensure that the battery black powder is completely separated from other materials and that the purity of the battery black powder is greater than 95%.

5. The classification recovery method according to claim 1, characterized in that: The process of carbonization, cracking and refining of lithium carbonate described in (7) is as follows: solid lithium carbonate is mixed with water to form a slurry, and CO2 is introduced from the bottom of the slurry during stirring. In the slurry, the weight ratio of solid lithium carbonate to water is not higher than 1:30, so as to ensure that low-purity lithium carbonate is fully dissolved and the purity of the introduced CO2 gas is not less than 99.99%.

6. The classification recovery method according to claim 1, characterized in that: (8) The ball milling frequency is 10-30 Hz, and the ball milling time is 120-300 minutes; The slurry obtained by wet ball milling was centrifuged at 8000 rpm for 5-10 minutes, washed with ethanol for 4-6 times to separate the leached residue powder and the composite solvent, and vacuum dried for more than 10 hours; The concentration of sulfuric acid in the leaching process is 1-3 mol / L, the solid-liquid ratio of the leached residue powder to the dilute sulfuric acid is 80-120 g / L, the reaction time is 200-300 minutes, and the temperature is 70-95°C; In the incinerator, the sodium phosphate solution forms sodium tripolyphosphate at an operating temperature of 500-600°C, forms sodium pyrophosphate at 600-700°C, forms trisodium phosphate at 700-800°C, and forms sodium hexametaphosphate at 800-850°C.

7. The classification recovery method according to claim 1, characterized in that: (4) Oxidative calcination: The black powder is calcined in air at 600°C for 240 minutes to completely convert the divalent iron ions into trivalent iron, thereby obtaining the calcined battery black powder; (5) Acid leaching of lithium: The battery black powder is added to sulfuric acid for leaching to obtain a lithium-containing leaching solution and a leaching residue containing iron phosphate and negative electrode graphite; the concentration of sulfuric acid is 0.5 mol / L, the solid-liquid ratio of black powder to dilute sulfuric acid is 80-120 g / L, the reaction time is 300 minutes, and the temperature is 95°C.

Citation Information

Patent Citations

  • Recycling treatment method of waste and old lithium iron phosphate battery anode materials

    CN102208706A

  • Treatment method for recycling waste lithium iron phosphate batteries

    CN113896211A

  • Pre-oxidation strategy applied to regeneration of lithium iron phosphate

    CN118545691A

  • Direct recovery method of retired lithium ion battery black powder

    CN118693385A

Cited By

  • Method for separating and recycling ferrophosphorus in battery recycling byproduct ferrophosphorus slag

    CN120157188A

  • Method for separating and recovering phosphorus and iron in phosphorus-iron slag as a byproduct of battery recycling

    CN120157188B

  • Method for preparing battery-grade lithium dihydrogen phosphate by recycling waste lithium iron phosphate battery

    CN120793861A

  • Method for efficiently recovering lithium and ferrous sulfate heptahydrate in retired lithium iron phosphate through total leaching and green impurity removal

    CN121247894A

  • Method for preparing lithium iron manganese phosphate from waste lithium iron phosphate

    CN121651317A